No evidence of impaired visual and tactile metacognition in adults with tourette disorder. (April 2022) - Arbuzova, Polina; Guo, Siqi; Koß, Christina; Kurvits, Lille; Faivre, Nathan; Kühn, Andrea A.; Filevich, Elisa; Ganos, Christos
Abstract: Introduction: Premonitory urges in Tourette disorder are often linked to altered somatosensory processing, which might include deficits in metacognition. We explored tactile and visual metacognitive ability in people with Tourette disorder and healthy control participants. Methods: Patients with Tourrete disorder and healthy control participants completed a tactile and a visual metacognitive task. On each trial, participants did a forced choice discrimination and then rated their confidence in their decision. To quantify metacognitive ability, we used m-ratio — a bias-free measure that allows for comparisons across modalities. Correlations between severity of tics and premonitory urges with tactile metacognitive sensitivity were also performed. Results: Metacognitive ability in both tactile and visual domains was comparable between adults with Tourette disorder and healthy controls. We also found no evidence for correlations between tactile metacognitive ability and severity of premonitory urges or tic severity. Conclusions: Tactile and visual metacognition is not impaired in adults with Tourette disorder. These results question the role of altered tactile metacognition in pathophysiology of tic disorders. Highlights: Tactile metacognition has been suggested to be involved in tic pathophysiology. We test tactile and visual metacognition in adults with Tourette disorder and controls. We found no group differences in measures of tactile and visual metacognition. Metacognitive performance was not associated to the severity of tics and urges.